Monitoring Child Growth and Development in Families at Risk of Stunting Using the Elsimil (Elektronik Siap Nikah dan Hamil) Application - Rohmah, Nikmatur; Kurniawan, Hendra; Savitri, Indah; Kuzairi, Untung; Febriansyah, Jauhari Ahmad; Afkarina, Izza; Ramadhani , Nova Risma; Maghfiro, Audrey Amalia Shakira (Universitas Nahdlatul Ulama Surabaya, 2023)
Bondowoso Regency have 14 priority communities by 2023 to accelerate stunting reduction, and Tamanan District is host to three of the fourteen villages. The objective of this community service is to implement the Elsimil application to track the growth and development of children from families at risk of stunting. This activity is an implementation of the Contextual Learning Model for Building Villages which integrated into the Pediatric Nursing Course. The team consists of 2 pediatric nursing lecturers and 34 nursing students. The methods used including monitoring children's growth and development, performing analyses, and educating families. Interviews, weight and height checks, developmental checks, and examination of family card records and KIA books are data collecting methods which then entered into the Elsimil program. This activity's population of interest is 31 families with children under the age of two in Tamanan District, devided into 3 villages: 9 children in Sumber Anom village, 11 children in Sumber Kemuning village, and the remaining 11 children in Kemirian village. This community service held in July-August 2023. Descriptive analysis is used in data analysis. Based on weight per age, 3.2% were severely underweight, 6.5% were underweight, 87.1% were normal weight, and 3.2% were at risk of being overweight. According to body length per age, 29% were severely stunted, 19.4% were short, and 51.6% were normal. A calculation of body weight per body length, 6.5% are extremely wasted, 3.2% are wasted, 64.5% are normal, 6.5% are at risk of being overweight, 3.2% are overweight, and 16.1% are obese. The results obtained based on body mass index per age were 3.2% severely wasted, 3.2% wasted, 64.5% good nutrition (normal), 16.1% at risk of overweight, 3.2% overweight, and 9.7% obesity. We conclude that this community service could optimize children monitoring and development by assisting stunted families through Elsimil application.